UPAYA MENINGKATKAN KEMAMPUAN BACA, TULIS DAN HITUNG MELALUI MODEL PEMBELAJARAN TEMATIK - Yakobus Ason (JURNAL PENDIDIKAN DASAR, 2014)
Abstract: The purpose of this research is the improvement of thematic learning model in order to increase the reading, writing and counting competency of first grade elementary student in Melawi regency. The subject of the research is the first grade student that include 11 students of Elementary School No.24 Teluk Batu and 15 students of Elementary School No.17 Laman Tanjung. In other hand, the object of this research is the implementation of thematic learning model and the reading- writing- and counting competency of the first grade elementary student. This research used the class action research method with the goal were the teacher, and the student of first grade elementary student. The results of this research are: (1) the first study in Elementary School No.24 shown that 64% of the students have reached the set up reading competency criteria with the score 70 above. The writing ability has reached 73% and the counting ability has reached 55% of the total students. (2) The second study in Elementary School No. 17 in Laman Tanjung shown that 87% of the students have reached the set up reading competency criteria with the score 70 above. The writing ability has reached 93% and counting ability has reached 80% of the total students. The observation of the learning process shown that in the first research there were 68.66% teachers used the arranged thematic learning model, where it was 73.77% in the second research. Therefore, the arranged thematic learning module has helped the teacher in the implementation thematic learning model so that can increase the competency in reading, writing and counting of grade 1 elementary students. Key Words: The ability improvement in reading, writing and counting, the module of thematic learning modelAbstrak: Tujuan penelitian ini adalah pengembangan model pembelajaran tematik untuk meningkatkan kompetensi Calistung siswa kelas I Sekolah Dasar di Kabupaten Melawi. Subyek penelitian adalah siswa kelas I SDN 24 Teluk Batu sebanyak 11 siswa dan SDN 17 Laman Tanjung sebanyak 15 siswa. Sedangkan obyek penelitian adalah penerapan model pembelajaran tematik dan kemampuan baca-tulis dan hitung siswa kelas I. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan sasarannya guru dan siswa kelas I sekolah dasar. Hasil pelatihan adalah sebagai berikut: (1) Pada penelitian pertama terhadap kompetensi membaca, menulis, dan berhitung siswa SDN 24 Teluk Batu menunjukkan bahwa kemampuan membaca adalah 64% dari jumlah siswa telah mencapai kriteria yang ditetapkan yakni memperoleh nilai 70 ke atas. Kemampuan menulis telah mencapai 73%, dan kemampuan berhitung mencapai 55% dari jumlah siswa; (2) Pada penelitian kedua terhadap kompetensi membaca, menulis, dan berhitung siswa SDN 17 Laman Tanjung menunjukkan bahwa kemampuan membaca adalah 87% dari jumlah siswa telah mencapai kriteria yang ditetapkan yakni memperoleh nilai 70 ke atas. Kemampuan menulis telah mencapai 93%, dan kemampuan berhitung mencapai 80% dari jumlah siswa. Hasil observasi terhadap proses pembelajaran guru mengunakan model pembelajaran tematik berdasarkan modul pembelajaran yang telah disusun adalah pada penelitian pertama telah mencapai 68,66%, sementara pada penelitian kedua mencapai 73,77% dengan demikian modul pembelajaran tematik yang telah disusun membantu guru dalam penerapan model pembelajaran tematik sehingga dapat meningkatkan kompetensi baca, tulis dan hitung siswa kelas I sekolah dasar.Kata Kunci: peningkatan kemampuan, baca, tulis dan hitung, modul model pembelajaran tematik.